Efficiency of Collaborative Computer Problem Solving by the Students of Adolescence and Youth: The Contribution of Social Intelligence - E.V. Gavrilova; E.A. Shepeleva; E.A. Valueva; M.R. Husnutdinova (Moscow State University of Psychology and Education, 2023)
The present study is focused on the measurement of the game efficiency by the younger adolescences in the individual and collaborative game problem solving conditions. The previously elaborated computer game system “PL-modified” was used. Social and emotional intelligence as well as gender factor were additionally controlled. 189 middle-school students from the 5—6th grades participated in this study. The results showed that game efficiency was higher in collaborative problem solving conditions (in comparison with the individual game) no matter which additional factor was controlled. Furthermore, the whole sample was divided in two groups by the criterion of the level of social intelligence of those participants who played in each pair. Thus, the group 1 included players with the equal level of social intelligence whereas the group 2 was presented by the gamers with the different levels of social intelligence. The pairs form the group 1 outperformed those participants from the group 2 in their game efficiency. Another independent resul concerns significant impact of social intelligence on the game performance in the pairs of boys. Emotional intelligence demonstrated only one significant positive correlation with the one parameter of game efficiency in the individual conditions. The present results are discussed in terms of the prospects of the usage of ‘PL- modified’ computer game system in the psychological studies conducted on the sample of young adolescents and taking their cognitive abilities into account.